2020
DOI: 10.1111/oik.07249
|View full text |Cite
|
Sign up to set email alerts
|

The island syndrome hypothesis is only partially validated in two rodent species in an inland–island system

Abstract: According to the island syndrome and island rule hypotheses, island isolation and reduced area lead to phenotypic shifts in ecologically relevant traits in insular populations compared to mainland ones. These hypotheses have been built up with oceanic islands in mind or islands where isolation is high and colonization rate relatively limited. This set of hypotheses, however, may not be applicable to other inland–island systems or recently fragmented landscapes. We investigated how island life leads to phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 67 publications
(78 reference statements)
2
19
0
Order By: Relevance
“…Masked shrews do not follow the classic island rule (i.e., small-bodied mammals increase in size on islands) since some insular populations appear to have decreased body mass compared to their mainland counterparts (e.g., Folinsbee, 1971). BPI masked shrews occur in high densities (Downie, 1986; Stewart et al, 1989; Telfer, 1984), which should lead to small animals having larger body size to better compete for resources (Juette et al, 2020). However, the discrepancy with this expected phenotype for island shrews might be due to their diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masked shrews do not follow the classic island rule (i.e., small-bodied mammals increase in size on islands) since some insular populations appear to have decreased body mass compared to their mainland counterparts (e.g., Folinsbee, 1971). BPI masked shrews occur in high densities (Downie, 1986; Stewart et al, 1989; Telfer, 1984), which should lead to small animals having larger body size to better compete for resources (Juette et al, 2020). However, the discrepancy with this expected phenotype for island shrews might be due to their diet.…”
Section: Discussionmentioning
confidence: 99%
“…The 'island rule' hypothesizes that smaller animals tend to increase in size, while larger ones tend to decrease in size on islands (Lomolino, 1985;Lomolino et al, 2013;van Valen, 1973). This pattern has been observed in mammoths (Palaeoloxodon falconeri) (Herridge & Lister, 2012) and deer mice (Peromyscus maniculatus) (Miller et al, 2021), but counter and ambiguous examples exist (Juette et al, 2020;Lokatis & Jeschke, 2018;Meiri et al, 2006Meiri et al, , 2008.…”
Section: Introductionmentioning
confidence: 96%
“…[ 62 ] argued how dispersal-related environmental filtering could be responsible for the higher explorativeness in island common frogs and tadpoles [ 62 ]. By contrast, deer mice ( Peromyscus maniculatus ) on islands in the Canadian Winnipeg River tended to be less explorative than mainland conspecifics, possibly reflecting differences between inland and oceanic island systems [ 67 ]. Camperio Ciani et al .…”
Section: The Current Evidence For a Behavioural Component To The Isla...mentioning
confidence: 99%
“…The empirical evidence on changes in aggression towards (but not necessarily limited to) conspecifics go either way. Reduced antagonism in island populations, as the result of high densities that make the monopolization of resources ineffective [ 124 ], was reported in five studies on a few rodent species ( P. maniculatus [ 68 , 69 ], Myodes gapperi [ 67 ] and M. musculus [ 77 ]) and birds [ 11 ]. Interestingly, Baier & Hoekstra [ 68 ] found that the difference faded in the F1 generation, indicating an important role for phenotypic plasticity [ 68 ].…”
Section: The Current Evidence For a Behavioural Component To The Isla...mentioning
confidence: 99%
See 1 more Smart Citation